2018
DOI: 10.1186/s12910-018-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in pragmatic randomized controlled trials: a review of the recent literature identifies gaps in ethical argumentation

Abstract: BackgroundPragmatic randomized controlled trials (RCTs) are designed to evaluate the effectiveness of interventions in real-world clinical conditions. However, these studies raise ethical issues for researchers and regulators. Our objective is to identify a list of key ethical issues in pragmatic RCTs and highlight gaps in the ethics literature.MethodsWe conducted a scoping review of articles addressing ethical aspects of pragmatic RCTs. After applying the search strategy and eligibility criteria, 36 articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 51 publications
(86 reference statements)
2
47
0
Order By: Relevance
“…In the present study we interviewed a range of stakeholders to explore their perspectives on ethical issues raised by pragmatic RCTs. The substantive areas of discussion were highly consistent with topics in the clinical trials literature, including risk [3234], consent [35, 36], the governance of research activities [24, 37, 38], the selection of study participants [39], the roles and responsibilities of different stakeholders [4042], and the publication and reporting transparency of trials [4346], but also indicated that the available literature on ethics in pragmatic RCTs is relatively narrow in its focus. Our findings suggest that not only do we need to discuss familiar topics (such as appropriate consent approaches and participant protections) in new ways, but also that there are new questions (such as the different roles and responsibilities of a broader range of stakeholders in pragmatic RCTs) that need to be addressed.…”
Section: Discussionmentioning
confidence: 83%
“…In the present study we interviewed a range of stakeholders to explore their perspectives on ethical issues raised by pragmatic RCTs. The substantive areas of discussion were highly consistent with topics in the clinical trials literature, including risk [3234], consent [35, 36], the governance of research activities [24, 37, 38], the selection of study participants [39], the roles and responsibilities of different stakeholders [4042], and the publication and reporting transparency of trials [4346], but also indicated that the available literature on ethics in pragmatic RCTs is relatively narrow in its focus. Our findings suggest that not only do we need to discuss familiar topics (such as appropriate consent approaches and participant protections) in new ways, but also that there are new questions (such as the different roles and responsibilities of a broader range of stakeholders in pragmatic RCTs) that need to be addressed.…”
Section: Discussionmentioning
confidence: 83%
“…However, a traditional randomized clinical trial is not feasible for the questions posed here and may be considered by some to be unethical. 20 , 39 , 40 Furthermore, physicians can change their behavior when directly observed or evaluated, whereas the vignette design creates a distance and is considered the most effective design for minimizing such effects. 20 …”
Section: Discussionmentioning
confidence: 99%
“…These studies are often cannot be performed because funds required to conduct these studies exceed the resources available to the researchers. One approach to overcome this problem may be by designing more streamlined randomized trials [106,107] however, even for such trials, the cost may still be an issue. One approach to address this issue may be the participation of the pharmaceutical industry by contributing more funds towards these trials.…”
Section: More Effective Funding Mechanismmentioning
confidence: 99%